2019
DOI: 10.1101/860528
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reverse-Engineering the Cortical Architecture for Controlled Semantic Cognition

Abstract: We present a ‘reverse engineering’ approach to deconstruct cognition into neurocomputational mechanisms and their underlying cortical architecture, using controlled semantic cognition as a test case. By systematically varying the structure of a computational model and assessing the functional consequences, we identified architectural properties necessary for generating the core functions of the semantic system. Semantic cognition presents a challenging test case as the brain must achieve two seemingly contradi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 68 publications
3
31
0
Order By: Relevance
“…A related issue concerning representational learning is the transfer (inductive generalization) of concepts in semantic cognition (e.g. reasoning from multiple instances of birds that all birds lay eggs; Abel et al, 2015;Jackson, Rogers, & Ralph, 2019;Ralph, Jefferies, Patterson, & Rogers, 2017). Here, we have argued that shared representation across tasks facilitates inference and transfer in control-dependent processing.…”
Section: Learning Memory and Semantic Cognitionmentioning
confidence: 69%
See 2 more Smart Citations
“…A related issue concerning representational learning is the transfer (inductive generalization) of concepts in semantic cognition (e.g. reasoning from multiple instances of birds that all birds lay eggs; Abel et al, 2015;Jackson, Rogers, & Ralph, 2019;Ralph, Jefferies, Patterson, & Rogers, 2017). Here, we have argued that shared representation across tasks facilitates inference and transfer in control-dependent processing.…”
Section: Learning Memory and Semantic Cognitionmentioning
confidence: 69%
“…Here, we have argued that shared representation across tasks facilitates inference and transfer in control-dependent processing. Similarly, in semantic cognition shared representation across stimulus modalities and contexts can achieve transfer of concepts (Jackson et al, 2019; T. T. Rogers & McClelland, 2004;Rumelhart et al, 1993). In their recent work, Jackson et al (2019) showed that the latter is facilitated in networks that allow information from different modalities to converge in the same "hub" for shared RATIONAL BOUNDEDNESS OF COGNITIVE CONTROL 167 representation.…”
Section: Learning Memory and Semantic Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, little is known about when and why people acquire shared representations across tasks. [66]. Similarly, architectural biases toward the learning of shared representation between tasks can accelerate the sequential acquisition of these tasks [65,68].…”
Section: The Benefits Of Shared Representations For Learningmentioning
confidence: 99%
“…If these regions are important for regulating semantic activation rather than storing involved (e.g., Rogers et al, 2004;O'Connor et al, 2009;Taylor et al, 2012;Schapiro et al, 2013). Conversely, there has been little formal modelling of semantic control processes (though for recent exceptions, see Hoffman et al, 2018;Jackson et al, 2019). The lack of established theoretical models makes it difficult to make precise predictions about how neural patterns in control regions should vary and how these areas might be distinguished from those that represent knowledge.…”
Section: Discussionmentioning
confidence: 99%